Lifelong learning journey for one AeU alumnus - The, Sun (The Sun, 2014)
AeU has over the years made improvement and modifications on the student portal, offering comprehensive learning materials and digital information that would come handy. All these allow students to have better scheduling, planning, and timing. - Yap, mentors as student at AeU